Blue economy impact and fishery comparative advantage mapping in Sulampua - Davani, Ifan (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
Abstract This research examines the impact of blue economy factors on economic growth in Sulampua. In this research, the blue economy variable is displayed by the fisheries sector which is proxied by the blue economy variable, which is represented by the fisheries sector which is proxied using marine capture fisheries production. This research used annual panel data at the provincial level in the Sulampua region covering the period 2018 to 2022. The analytical tool used in this research is panel data regression analysis using the Fixed Effect Model (FEM). The analysis results show that the blue economy factor significantly contributes to economic growth if a country's blue economy is well-mapped, integrated within a strong institutional framework, and based on concrete policies and research. In this way, spillover effects will be created, such as infrastructure growth, creating jobs, and helping to alleviate poverty through the social inclusion of residents of coastal areas. Based on Revealed Comparative Advantage (RCA), Maluku, South Sulawesi, and North Sulawesi have comparative advantages in fishery products compared to other provinces. Keywords: Blue Economy; Economic Growth; Sulampua; RCA Abstrak Penelitian ini mengkaji dampak faktor blue economy terhadap pertumbuhan ekonomi di Sulampua. Dalam penelitian ini variabel blue economy diwakili oleh sektor perikanan yang diproksikan dengan jumlah produksi perikanan tangkap laut. Penelitian ini menggunakan data panel tahunan tingkat provinsi di wilayah Sulampua selama periode tahun 2018 hingga 2022. Alat analisis yang digunakan dalam penelitian ini adalah analisis regresi data panel dengan menggunakan Fixed Effect Model (FEM). Hasil analisis menunjukkan bahwa faktor blue economy berkontribusi signifikan terhadap pertumbuhan ekonomi jika blue economy suatu negara terpetakan dengan baik, terintegrasi dalam kerangka kelembagaan yang kuat, dan didasarkan pada kebijakan dan penelitian yang konkrit. Dengan cara ini, akan tercipta spillover effects, seperti pertumbuhan infrastruktur, penciptaan lapangan kerja, dan membantu pengentasan kemiskinan melalui inklusi sosial penduduk wilayah pesisir. Berdasarkan Revealed Comparative Advantage (RCA), Maluku, Sulawesi Selatan, dan Sulawesi Utara mempunyai keunggulan komparatif produk perikanan dibandingkan provinsi lainnya. Kata Kunci: Ekonomi Biru; Pertumbuhan Ekonomi; Sulampua; RCA Kode klasifikasi JEL: Q18; Q23